A high-compatibility and high-strength PCABS alloy material and preparation method thereof

By modifying silica gluconic acid and mixing it with PP-g-MAH to prepare a compatibilizer, the stability and mechanical strength of the PCABS alloy material are improved, and the gloss of the material is reduced, which solves the problems of poor compatibility and high gloss between inorganic fillers and organic polymers in the prior art, and achieves a balanced effect of high strength and low gloss.

CN118879058BActive Publication Date: 2025-03-21GUANGDONG YONGXINHUA NEW MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411327299.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The compatibility of inorganic fillers and organic polymers in existing PCABS alloy materials is poor, resulting in reduced material stability and mechanical properties. At the same time, conventional materials have high gloss and strong reflectivity, which affects the visual effect of automotive interiors.

Method used

The silica is modified by gluconic acid and mixed with PP-g-MAH to prepare a compatibilizer to improve the affinity of the polymer resin and filler, thereby improving the stability and mechanical strength of the PCABS alloy material. At the same time, the gloss of the material is reduced by the use of the modified compatibilizer and achieving matte characteristics.

Benefits of technology

The stability and mechanical strength of PCABS alloy materials are improved, the gloss of the material is reduced, the requirements for low gloss are met in the fields of automotive interiors and other fields, and the problems of poor compatibility and high gloss in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 66F148B7E165E
    Figure 66F148B7E165E
  • Figure FDA0005237627740000011
    Figure FDA0005237627740000011
Patent Text Reader

Abstract

The present invention relates to a high-compatibility and high-strength PCABS alloy material and a preparation method thereof, wherein the high-compatibility and high-strength PCABS alloy material comprises the following components by mass: 40-60 parts of PC resin, 15-30 parts of ABS resin, 1-5 parts of modified compatibilizer, 5-10 parts of silica, and 3-5 parts of auxiliary agent; wherein the modified compatibilizer is a product of PP-g-MAH and modified silica after melt blending reaction; and the modified silica is a product of silica grafted with gluconic acid. The present invention effectively improves the affinity of polymer resin and filler, and promotes the improvement of various properties such as stability and mechanical strength of PCABS alloy. At the same time, the present invention has simple steps and low raw material cost, and solves the problems in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to a PCABS alloy material with high compatibility and high strength and a preparation method thereof. Background Art

[0002] PCABS alloy is a thermoplastic made by mixing polycarbonate (PC) and acrylonitrile-butadiene-styrene terpolymer (ABS). This type of material has excellent performance, combining the heat resistance and stability of PC resin with the processability of ABS resin, so it has many uses and is widely used in many fields such as electronics, electrical appliances, communications, and automobiles.

[0003] In current PCABS alloy materials, different functional fillers are usually added according to different uses, such as toughening fillers, thermal conductive fillers, flame retardant fillers, dielectric fillers, etc. However, inorganic fillers have poor compatibility with organic polymers, and multiple components are prone to agglomeration and uneven dispersion after mixing, resulting in reduced stability and mechanical properties of PCABS alloy products, and the additional functions brought by the fillers are not ideal.

[0004] In addition, conventional PCABS materials have high gloss and strong reflectivity, which can cause glare and interfere with vision in applications such as automotive interiors, posing a threat to the safety of passengers. How to use matte fillers to reduce the reflectivity of PCABS while ensuring the original performance of the alloy material is also a difficult problem faced by this field.

[0005] Currently, there are many modification methods for inorganic fillers that can improve the compatibility of fillers with organic resins. However, most technical solutions use silane coupling agents or organic polymers to graft and modify the fillers. The above methods not only have high raw material costs, but also complex modification steps and harsh reaction conditions. Therefore, they are difficult to be applied on a large scale in actual production and still have many limitations.

[0006] In summary, it is urgent to develop a new technical solution to solve the problems existing in the prior art. Summary of the invention

[0007] Based on this, the present invention develops a PCABS alloy material with high compatibility and high strength and a preparation method thereof. The present invention uses gluconic acid to modify silicon dioxide, and then mixes it with PP-g-MAH to prepare a compatibilizer, which effectively improves the affinity between the polymer resin and the filler, and promotes the improvement of various properties such as stability and mechanical strength of the PCABS alloy. At the same time, the present invention has simple steps and low raw material cost, and solves the problems in the prior art.

[0008] An object of the present invention is to provide a PCABS alloy material with high compatibility and high strength, wherein the PCABS alloy material with high compatibility and high strength comprises the following components in parts by mass:

[0009] PC resin 40-60 parts

[0010] ABS resin 15-30 parts

[0011] 1-5 parts of modified compatibilizer

[0012] Silicon dioxide 5-10 parts

[0013] 3-5 parts of additives;

[0014] in,

[0015] The modified compatibilizer is a product of melt blending reaction of PP-g-MAH and modified silicon dioxide;

[0016] The modified silicon dioxide is a product of silicon dioxide grafted with gluconic acid.

[0017] Furthermore, the auxiliary agent is selected from one or more of an antioxidant, a lubricant, and an anti-ultraviolet agent.

[0018] Furthermore, the preparation method of the modified silicon dioxide is:

[0019] Silicon dioxide and gluconic acid are mixed and ultrasonically heated to obtain modified silicon dioxide.

[0020] Furthermore, the mass ratio of silicon dioxide to gluconic acid is 1:10-20.

[0021] Furthermore, the temperature of the ultrasonic heating is 30-60°C.

[0022] Furthermore, the preparation method of the modified compatibilizer is: PP-g-MAH and modified silica are blended and added into an extruder, heated and melted, extruded and granulated to obtain the modified compatibilizer.

[0023] Furthermore, the mass ratio of the PP-g-MAH to the modified silica is (0.5-5):1.

[0024] Furthermore, the heating and melting temperature is 160-180°C.

[0025] Another object of the present invention is to provide a method for preparing the above-mentioned high-compatibility and high-strength PCABS alloy material, wherein the method for preparing the high-compatibility and high-strength PCABS alloy material comprises the following steps:

[0026] PC resin, ABS resin, modified compatibilizer, silica and additives are mixed, added into an extruder, melt-extruded and granulated at 230-260° C. to obtain a PCABS alloy material with high compatibility and high strength.

[0027] The present invention has the following beneficial effects:

[0028] 1. The present invention provides a PCABS alloy material with high compatibility and high strength and a preparation method thereof. The PCABS alloy material with high compatibility and high strength contains a modified compatibilizer. The component firstly mixes silica with gluconic acid for ultrasonic reaction, so that gluconic acid is grafted on the surface of silica, and a large number of active hydroxyl groups are introduced. Then, the modified silica is mixed with PP-g-MAH for melting reaction, so that the active hydroxyl groups further react with carboxyl groups, thereby grafting silica in PP-g-MAH to obtain a modified compatibilizer. The modified compatibilizer of the present invention is not only conducive to enhancing the compatibility between PC resin and ABS resin, but also effectively improves the affinity between inorganic filler and PCABS resin. The components can form a stable three-dimensional structure through chemical bonds, hydrogen bonds, and intermolecular forces, so that the alloy material has better stability and mechanical strength, and is suitable for a wider range of application scenarios, which is of great significance to the further development of PCABS alloy materials.

[0029] 2. The ABS275 resin and silica of the present invention have low gloss. After adding the modified compatibilizer, a more uniform and stable distribution and bonding state can be achieved, which is beneficial to further reduce the reflection of light while improving the mechanical properties, thereby achieving the low gloss matte characteristics of the alloy material, meeting the performance requirements of automotive interiors and other fields with low gloss requirements. DETAILED DESCRIPTION

[0030] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0031] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0032] It should be understood that, except in any operating examples, or otherwise indicated, the amounts of ingredients used in the specification or all numbers, for example, should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification are approximate values ​​that vary according to the desired properties to be obtained by the present invention.

[0033] The grade of PC resin in the embodiment of the present invention is PC IR2200.

[0034] The ABS resin grade in the embodiment of the present invention is ABS275.

[0035] The particle size of the silicon dioxide in the embodiment of the present invention is 100 nm.

[0036] The PP-g-MAH brand in the embodiment of the present invention is Arkema CA100.

[0037] The auxiliary agent in the embodiment of the present invention includes antioxidant 1010 and anti-ultraviolet agent UV327 in a mass ratio of 1:1.

[0038] The "parts" in the embodiments of the present invention refer to parts by mass.

[0039] The preparation method of the modified compatibilizer in the embodiment of the present invention comprises the following steps:

[0040] S1. Add 10 parts of silicon dioxide and 15 parts of gluconic acid to 50 parts of water, perform ultrasonic reaction at 60°C for 10 h, filter and dry to obtain modified silicon dioxide;

[0041] S2. 5 parts of PP-g-MAH and 1.5 parts of the modified silica are blended and added into an extruder. The mixture is heated to melt at 180° C. and granulated after extrusion to obtain a modified compatibilizer.

[0042] Example 1

[0043] A PCABS alloy material with high compatibility and high strength, comprising the following components in parts by mass:

[0044] PC resin 40 parts

[0045] ABS resin 15 parts

[0046] 3 parts of modified compatibilizer

[0047] 5 parts of silicon dioxide

[0048] 3 parts of additives;

[0049] The preparation method of the highly compatible and high-strength PCABS alloy material comprises the following steps:

[0050] According to the above mass fractions, PC resin, ABS resin, modified compatibilizer, silica and additives are mixed, added into a twin-screw extruder, melt-extruded and granulated at 230° C. to obtain a PCABS alloy material with high compatibility and high strength.

[0051] Example 2

[0052] A PCABS alloy material with high compatibility and high strength, comprising the following components in parts by mass:

[0053] PC resin 60 parts

[0054] ABS resin 30 parts

[0055] 5 parts of modified compatibilizer

[0056] Silicon dioxide 9 parts

[0057] 5 parts of additives;

[0058] The preparation method of the highly compatible and high-strength PCABS alloy material comprises the following steps:

[0059] According to the above mass fractions, PC resin, ABS resin, modified compatibilizer, silica and additives are mixed, added into a twin-screw extruder, melt-extruded and granulated at 230° C. to obtain a PCABS alloy material with high compatibility and high strength.

[0060] Example 3

[0061] A PCABS alloy material with high compatibility and high strength, comprising the following components in parts by mass:

[0062] PC resin 55 parts

[0063] ABS resin 25 parts

[0064] 4 parts of modified compatibilizer

[0065] 7 parts of silicon dioxide

[0066] 4 parts of additives;

[0067] The preparation method of the highly compatible and high-strength PCABS alloy material comprises the following steps:

[0068] According to the above mass fractions, PC resin, ABS resin, modified compatibilizer, silica and additives are mixed, added into a twin-screw extruder, melt-extruded and granulated at 230° C. to obtain a PCABS alloy material with high compatibility and high strength.

[0069] Comparative Example 1

[0070] A PCABS alloy material. The difference between this comparative example and Example 1 is that in the preparation method of the modified compatibilizer, step S1 is deleted, and the modified silicon dioxide in step S2 is replaced by hydroxylated silicon dioxide. The preparation method of the hydroxylated silicon dioxide is as follows: the silicon dioxide is immersed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide (the concentration of hydrogen peroxide is 30 wt%) in a mass ratio of 7:3, treated at 70° C. for 1 h, and washed and dried to obtain the hydroxylated silicon dioxide. The other components and preparation method are the same as those in Example 1.

[0071] Comparative Example 2

[0072] A PCABS alloy material. The difference between this comparative example and Example 1 is that in the preparation method of the modified compatibilizer, step S1 is deleted, and the modified silicon dioxide in step S2 is replaced by a physical mixture of silicon dioxide and gluconic acid in a mass ratio of 10:15. The other components and preparation method are the same as those in Example 1.

[0073] Test Case

[0074] Test method:

[0075] The PCABS alloy materials prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, and the glossiness was tested according to ASTM-D523-2014, and the tensile strength, flexural strength, and notched impact strength were measured according to ISO 527, ISO 178, ISO 179, and other standards.

[0076] The test results are shown in Table 1.

[0077] Table 1 Performance test results

[0078]

[0079] According to Table 1, it can be concluded that the highly compatible and high-strength PCABS alloy materials prepared in Examples 1-3 have excellent mechanical properties, and the tensile strength, bending strength and notched impact strength are significantly better than those of the comparative examples, while the glossiness is relatively low. In Comparative Example 1, the silica grafted with gluconic acid is replaced with conventional hydroxylated silica, the number and density of the introduced hydroxyl groups are reduced, the degree of reaction with PP-g-MAH is reduced, and the volume expansion effect is reduced, while in Comparative Example 2, silica is directly mixed with gluconic acid without grafting modification, which affects the effect of the volume expander, causing the performance of the alloy material to be significantly reduced, and the glossiness is significantly increased. In summary, the highly compatible and high-strength PCABS alloy material of the present invention overcomes the defects existing in the prior art and has good application prospects.

[0080] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered as exemplary and non-restrictive in all respects.

[0081] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A PCABS alloy material with high compatibility and high strength, characterized in that: The highly compatible and high-strength PCABS alloy material comprises the following components in parts by mass: in, The modified compatibilizer is a product of melt blending reaction of PP-g-MAH and modified silicon dioxide; The modified silicon dioxide is a product of silicon dioxide grafted with gluconic acid; The preparation method of the modified silicon dioxide is: The silicon dioxide and gluconic acid are mixed and ultrasonically heated to obtain modified silicon dioxide; The preparation method of the modified compatibilizer is as follows: PP-g-MAH and modified silica are blended and added into an extruder, heated and melted, and granulated after extrusion to obtain the modified compatibilizer; The mass ratio of the PP-g-MAH to the modified silica is (0.5-5):

1.

2. The PCABS alloy material with high compatibility and high strength according to claim 1, characterized in that: The auxiliary agent is selected from one or more of an antioxidant, a lubricant, and an anti-ultraviolet agent.

3. The PCABS alloy material with high compatibility and high strength according to claim 1, characterized in that: The mass ratio of the silicon dioxide to the gluconic acid is 1:10-20.

4. The PCABS alloy material with high compatibility and high strength according to claim 1, characterized in that: The temperature of the ultrasonic heating is 30-60°C.

5. The PCABS alloy material with high compatibility and high strength according to claim 4, characterized in that: The heating and melting temperature is 160-180°C.

6. The method for preparing the highly compatible and high-strength PCABS alloy material according to any one of claims 1 to 5, characterized in that: The preparation method of the highly compatible and high-strength PCABS alloy material comprises the following steps: PC resin, ABS resin, modified compatibilizer, silica and additives are mixed, added into an extruder, melt-extruded and granulated at 230-260° C. to obtain a PCABS alloy material with high compatibility and high strength.

Citation Information

Patent Citations

  • Phosphate flame-retardant PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) alloy and preparation method thereof

    CN104017343A

  • Impact-resistant weather-resistant flame-retardant polypropylene resin used for light fittings

    CN104177697A

  • Composite nano silicon dioxide modified PC / ABS alloy material and preparation method thereof

    CN113817304A

  • High-toughness PCABS alloy material and preparation method thereof

    CN116925517A

  • Preparation method of reactive blending toughened polylactic acid starch compound

    CN117511155A